Capsaicin 8% Patch for Spinal Cord Injury Focal Neuropathic Pain, a Randomized Controlled Trial. Issue 1 (7th July 2022) - Olusanya, Adedeji; Yearsley, Aaron; Brown, Nicholas; Braun, Samantha; Hayes, Corey; Rose, Evon; Connolly, Brian; Dicks, Madeline; Beal, Colby; Helmonds, Brett; Peace, Wesley; Kirkman, Bryce; et al.
Abstract: Background: Neuropathic pain (NP) after spinal cord injury (SCI) exacerbates disability, decreases quality of life (QOL), and is often refractory to available therapies. Patients report willingness to trade potential recovery of strength, bowel, bladder, or sexual function for pain relief. One proposed mechanism causing NP is up-regulation of transient receptor potential vanilloid 1 (TRPV 1) proteins in uninjured C fibers and dorsal root ganglia causing neuronal excitability. Recent studies have found up-regulation of TRPV 1 proteins after SCI. Objective: We hypothesize the application of capsaicin 8% patch (C8P), FDA approved for NP in diabetic peripheral neuropathy and post-herpetic neuralgia, will improve pain, function and QOL in persons with SCI. Methods: Randomized single-blind crossover design in which 11 persons with SCI and NP refractory to two oral pain medications received C8P or a control low dose Capsaicin 0.025% patch (CON) over two 12-week periods. Pain (VAS, MPI-SCI), quality of life (WHO-QOL), and functional status (SCIM) were measured at 2–4-week intervals. Results: There was a main treatment effect of C8P over CON on VAS and MPI-SCI outcomes with pain reduction of 35% and 29% at weeks 2 and 4, respectively. C8P also demonstrated a main treatment effect over CON on the SCIM mobility subscale. WHO-QOL scores did not improve with C8P. Conclusions: C8P improves pain and mobility for patients with SCI and refractory NP. Larger studies should be performed to evaluate impact of repeat applications and QOL outcomes.